2010
DOI: 10.1042/bst0381709
|View full text |Cite
|
Sign up to set email alerts
|

Ran control of mitosis in human cells: gradients and local signals

Abstract: Roles of the GTPase Ran in cell life and division rely on a largely conserved mechanism, i.e. Ran's ability to interact with transport vectors. Modes of control of downstream factors, however, are diversified at particular times of the cell cycle. Specificity and fine-tuning emerge most clearly during mitosis. In the present article, we focus on the distinction between global mitotic control by the chromosomal Ran gradient and specific spatial and temporal control operated by localized Ran network members at s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…TPX2 gene is localized on chromosomal band 20q11, a region of frequent amplification with a strong correlation between copy number and protein expression levels [44], [45]. In addition, the important contribution of RAN to the mitotic process has also been well described [46]. Here, we report that TPX2 expression, like RAN, correlates positively with tumor grade, and was associated with poor patient survival and with a short recurrence time in HG serous EOC (Figures 2–4).…”
Section: Discussionsupporting
confidence: 58%
“…TPX2 gene is localized on chromosomal band 20q11, a region of frequent amplification with a strong correlation between copy number and protein expression levels [44], [45]. In addition, the important contribution of RAN to the mitotic process has also been well described [46]. Here, we report that TPX2 expression, like RAN, correlates positively with tumor grade, and was associated with poor patient survival and with a short recurrence time in HG serous EOC (Figures 2–4).…”
Section: Discussionsupporting
confidence: 58%
“…Excellent reviews of a number of seminal in vivo studies on the karyopherin/Ran dueling regulators by the Lavia group and others include [64,104]. Recently, Hasegawa et al [105] found a steep RanGTP gradient exists around the mitotic chromosomes of rapidly growing cells, while reduced RanGTP gradients are observed around the chromosomes in primary cells (HFF-1 cells).…”
Section: In Vivo Evidencementioning
confidence: 99%
“…Moreover, CRM1 has additional effects on the definition of kinetochore fibers and in chromosome segregation during mitosis. In particular, CRM1 activity in metaphase and later anaphase changes repartitioning of RanGTP and consequently also of effectors on kinetochores and centrosomes [ 63 , 64 , 65 , 66 , 67 , 68 , 69 ].…”
Section: The Nucleocytoplasmic Transport Machinerymentioning
confidence: 99%